Nekotorye psikhofiziologicheskie osobennosti basketbolistov i regbistov (sravnitel'nye kharakteristiki) - Skvortsov, M. V. (Teorija i Praktika fiziceskoj Kul'tury, 1997)
The purpose of this study was to reveal the peculiarities of mental working capacity, differentiated inhibition, nervous processes lability and capacity of the optic analyzer. The comparative analysis of mental working capacity in basketball and rugby players had shown the advantage of the first ounes. The lability of nervous processes and the capacity of the optic analyzer are almost equal in both sports specializations.